Kellers Medien Formen - Genres - Institutionen - Berndt, Frauke (Gottfried Kellers Moderne, 2022)
As an author and painter, Gottfried Keller deliberately experimented with different media and their forms - with genres from both literature and the fine arts. The objective of this volume is to trace the various intermedial and transmedial connections in Keller's oeuvre, focusing on the processes of literary and social institutionalization that accompanied his experiments with form and genre.